Inmunoglobulina E anti-Plasmodium en niños de Urabá (Colombia) según la presencia de malaria (2013)
ABSTRACT: We are not aware of studies in Colombia on levels of specific IgE in children without malaria and only one is available in children with uncomplicated malaria. Objective: To measure anti-Plasmodium IgE in children with or without malaria according to sex, nutritional status, and the presence of intestinal helminthes, and the relations with hematologic variables. Methodology: anti-Plasmodium IgE was measured in 335 children without malaria and in 125 with uncomplicated malaria (P. vivax: 116; P. falciparum: 9). Measurement was done with the ELISA technique, with a crude antigen extract of P. falciparum FCB-2 strain. We used Sigma`s conjugated anti-anti-IgE A3525. IgE was measured and expressed as optical density (absorbance). Results: Anti-Plasmodium IgE in children without malaria was 0.808 ± 0.508 (cutoff point used to define high level: 0.584) and 1.968 ± 1.237 in children with malaria (p = 0.000000). Anti-Plasmodium IgE levels showed no significant difference according to plasmodial species but there was significant difference by sex and nutritional status. In children without malaria, the level of anti-Plasmodium IgE was higher in those with the presence of roundworm, whipworm and hookworm, but the difference was significant only for roundworms. The level of anti-Plasmodium IgE showed significant positive linear correlation with the number of eggs of Ascaris and whipworm per gram of stool. Conclusions: In Urabá, children with or without malaria have elevated levels of anti-Plasmodium IgE, that are higher in women and in those affected by malaria.